Central Bank Policy Mix: Issues, Challenges, and Policy Responses Handbook of Central Banking Studies - Warjiyo, Perry; Juhro, Solikin M. (Springer Nature, 2022)
This is an open access book. This book is an integration of keynote speeches, lectures, and related teaching materials during the five years of the "Central Bank Policy Mix: Issues, Challenges and Policy Responses" flagship program of the BI Institute, the learning and research centre of Bank Indonesia. The book examines the interactions among central bank policies including monetary policy, exchange rate policy, macroprudential policy, and capital flow management and also elaborates on modeling issues and quantitative analysis of the interaction between macroeconomic variables and policy instruments.